Porous calcium-doped hematite as well as preparation method and application thereof

Through the preparation and application of porous calcium-doped hematite, the adsorption capacity of hematite and the calcium-doped is used to solve the problem of cadmium pollution rebound, and the rapid and stable adsorption and complete stability of cadmium are achieved. Ensures stability under acidic conditions.

CN119430298APending Publication Date: 2025-02-14NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411828412.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, when cadmium is contaminated in fixed soil, the problem of cadmium pollution rebound caused by changes in environmental conditions has not been effectively solved, especially in acidic conditions, which is difficult to achieve complete stability of cadmium.

Method used

Porous calcium-doped hematite is used to enrich cadmium on the surface through hematite as the host mineral, and its adsorption capacity is used to enrich cadmium on the surface, and the internal structure of calcium-doped modified hematite is achieved to achieve homocrystalline replacement of cadmium and calcium, fixed Cadmium is in the lattice.

Benefits of technology

The rapid and stable adsorption and complete stability of cadmium ions are achieved. The material structure remains stable under acidic conditions, making it difficult to release cadmium again, significantly reducing the bioavailability of cadmium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430298A_ABST
    Figure CN119430298A_ABST
Patent Text Reader

Abstract

The invention relates to porous calcium-doped hematite and a preparation method and application thereof.The hematite is modified through calcium doping, calcium ions are doped into a hematite crystal structure, a silicon dioxide nanosphere is used as a hard template to etch a material into a porous structure, and the porous calcium-doped hematite is prepared on the basis of the structural characteristics. The porous calcium-doped hematite not only can realize rapid adsorption of cadmium ions, but also can realize isomorphous substitution of the cadmium ions and calcium ions in a crystal structure, so that fixation of cadmium in crystal lattices is realized. The porous calcium-doped hematite can be used for removing cadmium pollution in the rice field, complete stabilization of cadmium ions can be achieved through isomorphous substitution, the structure of the material is still kept stable under the acidic condition, and cadmium is difficult to release again.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to porous calcium-doped hematite and a preparation method and application thereof. Background Art

[0002] Solidification / stabilization technology is a common method for remediation of soil heavy metal pollution. This technology will not significantly change the physical and chemical structure of the soil and is suitable for the remediation of contaminated farmland soil. At present, most cadmium-contaminated soil remediation is achieved through adsorption, precipitation and co-precipitation. Various metal minerals (such as goethite, hematite) and non-metallic minerals (such as calcite, zeolite, phosphate) and other stabilization materials have been proven to effectively fix cadmium in soil. Although these materials reduce the cadmium concentration of exchangeable components in the soil in the short term, the rebound problem of cadmium pollution caused by solid phase dissolution or desorption caused by changes in environmental conditions has not been well solved. For example, paddy soil is an environment with alternating flooding and drainage cycles. During the flooding period, cadmium is mainly adsorbed on the surface of soil minerals. In the drainage period, due to the decrease in pH, a large amount of cadmium is released and exists in a free state. It is easy to enter the plant body through the root system, increasing the risk of cadmium enrichment in rice grains.

[0003] Compared with surface adsorption and precipitation, fixing heavy metal ions in mineral lattices can resist changes in environmental conditions to a large extent and always maintain low bioavailability. The current technology to achieve this process mainly uses hydrotalcite as a host mineral, and anchors heavy metal ions in the mineral lattice through isomorphous substitution or dissolution-reconstruction, thereby achieving long-term fixation. Although the solubility product constant of the hydrotalcite structure formed after enrichment of heavy metals is smaller than that of the corresponding hydroxide and carbonate minerals, hydrotalcite is a weakly alkaline mineral and its stability decreases under acidic conditions, especially in southern my country where paddy soil is generally acidic. Minerals may dissolve, causing the fixed cadmium to be released again. In addition, the removal of heavy metal ions by hydrotalcite often includes multiple pathways such as adsorption, induced surface precipitation, and isomorphous substitution, making it difficult to achieve complete stabilization of heavy metal ions. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a porous calcium-doped hematite and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is: a method for preparing porous calcium-doped hematite, which comprises mixing iron salt, calcium salt and a hard template, adjusting the pH value to 12, and performing a crystallization reaction at 180° C. The obtained product is treated with acid and alkali to remove the hard template in the crystal structure, thereby obtaining porous calcium-doped hematite.

[0006] Preferably, the hard template is monodisperse silica nanoparticles.

[0007] Preferably, anhydrous ethanol and tetraethyl orthosilicate are mixed in a volume ratio of 20:1 to prepare solution A; anhydrous ethanol and aqueous ammonia are mixed in a volume ratio of 15.5:1 to prepare solution B; A:B:water is mixed in a volume ratio of 6:6.6:1, and the reaction is stirred at 30°C for 12 hours to obtain monodisperse silica nanoparticles that can be used as a hard template.

[0008] Preferably, it is characterized in that the specific steps are as follows:

[0009] Step 1: Anhydrous ethanol and tetraethyl orthosilicate are mixed in a volume ratio of 20:1 to prepare solution A; Anhydrous ethanol and ammonia water are mixed in a volume ratio of 15.5:1 to prepare solution B; A: B: water are mixed in a volume ratio of 6: 6.6: 1, water is added to solution B to form a mixed solution, and solution A is then added dropwise to the mixed solution, and the reaction is stirred at 30°C for 12 hours to obtain monodisperse silica nanoparticles that can be used as a hard template;

[0010] Step 2: adding ferric chloride and calcium chloride to ethanol, wherein the total metal ion concentration is 0.2 mol / L, and the molar ratio of iron ion to calcium ion is 85-95:15-5; preferably 85:15; adding monodisperse silica nanoparticles to the mixed solution, ultrasonically mixing, and adjusting the pH value to 12 by sodium hydroxide;

[0011] Step 3: The suspension was transferred into a reactor and reacted at 180°C for 24 hours; the obtained solid material was added into 0.25 mol / L HCl and immersed for 30 minutes;

[0012] Step 4: Add the solid product into a 2 mol / L sodium hydroxide solution, immerse for 12 h to obtain a porous structure, and dry to obtain calcium-modified hematite.

[0013] A porous calcium-doped hematite is based on hematite, calcium ions are doped into the crystal structure, and a porous structure is formed by etching.

[0014] Preferably, it is prepared by a calcium-modified hematite preparation method.

[0015] Application of porous calcium-doped hematite in decontamination of agricultural soil.

[0016] Preferably, it is used for removing cadmium pollution in rice fields.

[0017] The advantages and positive effects of the present invention are: providing a material capable of rapidly and stably adsorbing cadmium ions; using hematite as a host mineral, utilizing the adsorption capacity of hematite itself to rapidly enrich free cadmium on the surface of the material, and then modifying the internal structure of the hematite by calcium doping, so that the cadmium ions and the calcium in the structure undergo isomorphous substitution, thereby achieving the fixation of cadmium in the crystal lattice;

[0018] Porous calcium-doped hematite can achieve complete stabilization of cadmium ions through isomorphous substitution. The structure of the material remains stable under acidic conditions, and cadmium is difficult to release again. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Electron micrograph of monodisperse silica nanoparticles;

[0020] Figure 2 Scanning electron microscopy image of synthesized porous calcium-doped hematite;

[0021] Figure 3 Transmission electron microscopy image of synthesized porous calcium-doped hematite;

[0022] Figure 4 Nitrogen adsorption-desorption curves of synthesized porous calcium-doped hematite;

[0023] Figure 5 Pore ​​size distribution of synthesized porous calcium-doped hematite;

[0024] Figure 6 Synthesize XRD patterns of different materials;

[0025] Figure 7 Fixation of cadmium ions by porous calcium-doped hematite;

[0026] Figure 8 Fixation of cadmium ions by hematite;

[0027] Fig. 9 Fixation of cadmium ions by calcium-doped hematite;

[0028] Fig.10 Fixation of cadmium ions by porous hematite;

[0029] Fig.11 Adsorption isotherms of cadmium immobilized by different materials;

[0030] Fig.12 The amount of cadmium fixed in the structure of (porous) hematite with different calcium doping levels. DETAILED DESCRIPTION

[0031] The embodiments of the present invention are described below with reference to the accompanying drawings.

[0032] The invention relates to a porous calcium-doped hematite and a preparation method and application thereof. The calcium ions are incorporated into the crystal structure of the hematite by calcium doping and modifying the hematite. Based on such structural characteristics, the calcium-modified hematite can not only realize rapid adsorption of cadmium ions, but also realize isomorphous substitution of cadmium ions with calcium ions in the crystal structure, thereby realizing fixation of cadmium in the crystal lattice.

[0033] Hematite is a thermodynamically stable iron oxide that can maintain a stable structure and not dissolve under acidic conditions. It has a good ability to adsorb heavy metals. The isomorphous substitution mechanism is an effective means to fix foreign heavy metal ions in the mineral structure. The position occupied by a certain ion or atom in the crystal structure can be partially occupied by other ions or atoms with similar properties and sizes, but the crystal structure remains basically unchanged. 3+ and Cd 2+ The ionic radius of Cd 2+ It is impossible to enter the iron oxide structure by isomorphous substitution. Ca 2+ and Cd 2+ The ionic radius and chemical properties of calcium-based minerals are similar, but calcium-based minerals have problems such as poor stability in actual environmental remediation. The present invention selects hematite as the host mineral and introduces Ca 2+ , synthesizing calcium-doped hematite, thereby achieving ultra-stable fixation of cadmium. Since the hydrothermally synthesized hematite is a block structure with a small specific surface area, the amount of cadmium fixed and the utilization rate of calcium in the structure are low, so the hard template method is used to etch the material into a porous structure.

[0034] The preparation method of calcium-modified hematite is as follows:

[0035] Step 1: Preparation of monodisperse silica nanoparticles; Anhydrous ethanol and tetraethyl orthosilicate are mixed in a volume ratio of 20:1 to prepare solution A; Anhydrous ethanol and ammonia water are mixed in a volume ratio of 15.5:1 to prepare solution B; A: B: water are mixed in a volume ratio of 6: 6.6: 1; Specifically, 16.5 ml of solution B can be measured, 2.5 ml of water can be added to form a mixed solution, and then 15 ml of solution A can be added dropwise to the mixed solution, and the reaction is stirred at 30°C for 12 hours to finally obtain monodisperse silica nanoparticles that can be used as a hard template; wherein, adding an appropriate amount of water can promote the hydrolysis of tetraethyl orthosilicate, while ensuring that the silica nanoparticles will not be too agglomerated and maintain an appropriate size, which is conducive to the preparation of monodisperse silica nanoparticles;

[0036] Step 2: adding ferric chloride and calcium chloride to ethanol, the total metal ion concentration is 0.2 mol / L, and the molar ratio of iron ion to calcium ion is 85-95:15-5; adding monodisperse silica nanoparticles to the mixed solution, ultrasonically mixing, and adjusting the pH value to 12 with sodium hydroxide;

[0037] Step 3: The suspension is transferred into a reactor and crystallized at 180°C for 24 hours; after cooling to room temperature, a solid product is obtained by centrifugation; the solid material is added into 0.25 mol / L HCl and immersed for 30 minutes to remove poorly crystallized iron oxides and adsorbed calcium;

[0038] Step 4: Add the solid product into a 2 mol / L sodium hydroxide solution and immerse for 12 hours to remove the silica nanoparticles and obtain a porous structure; wash with deionized water and dry to obtain porous calcium-doped hematite.

[0039] The porous calcium-doped hematite prepared by the above method can be used for the adsorption and fixation of cadmium ions. On the one hand, the modified hematite can achieve rapid adsorption of cadmium ions, and on the other hand, the Cd 2+ Ca of similar size and properties 2+ It can undergo isomorphous substitution with cadmium ions, allowing cadmium to enter the crystal structure of modified hematite without destroying the crystal structure of calcium-modified hematite, thereby achieving the purpose of stabilizing and fixing cadmium ions.

[0040] When in use, the prepared porous calcium-doped hematite is put into a liquid sample containing cadmium ions to achieve the adsorption and fixation of cadmium ions. Experimental verification shows that porous calcium-doped hematite can quickly adsorb cadmium ions, and no cadmium ions are seen to be detached after being placed for 120 hours, proving that porous calcium-doped hematite has excellent stability after adsorbing cadmium ions.

[0041] The scheme of the present invention is described below in conjunction with the accompanying drawings, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.

[0042] Example 1: Preparation of monodisperse silica nanoparticles

[0043] Solution A was prepared by mixing anhydrous ethanol and tetraethyl orthosilicate in a volume ratio of 20:1; solution B was prepared by mixing anhydrous ethanol and aqueous ammonia in a volume ratio of 15.5:1. Measure 16.5 ml of solution B, add 2.5 ml of water to form a mixed solution, and then add 15 ml of solution A dropwise to the mixed solution, and react at 30°C for 12 hours with constant stirring. After the reaction is completed, the solid substance produced by the reaction is obtained by centrifugation, and then washed alternately with deionized water and anhydrous ethanol three times. After drying, the solid powder obtained is monodisperse silica nanoparticles, which can be used as a hard template. The electron microscope image of monodisperse silica nanoparticles is shown below. Figure 1 As shown, it can be seen that the monodispersed silica nanoparticles are uniformly spherical.

[0044] Example 2: Preparation of porous calcium-doped hematite

[0045] Weigh 9.2g of ferric chloride hexahydrate and 0.67g of anhydrous calcium chloride (Ca / (Fe+Ca)=15mol%), dissolve in 200ml96% ethanol; add 0.3g of monodisperse silica nanoparticles prepared in Example 1 to the mixed solution, mix ultrasonically for 1 hour, add 2mol / L sodium hydroxide solution to adjust the pH of the mixed solution to 12, transfer the resulting suspension into a reactor, and crystallize at 180°C for 24h. After the reaction is completed, cool the mixed solution to room temperature and centrifuge to obtain the solid material produced by the reaction. Soak in 0.25mol / L HCl for 10min to remove poorly crystallized iron oxides and adsorbed calcium; then soak in 2mol / L sodium hydroxide for 12h to remove the silica nanoparticles to obtain a porous structure; wash with deionized water and dry to obtain porous calcium-doped hematite. The microstructure of porous calcium-doped hematite is as follows Figure 2-Figure 5 As shown in the figure, the synthesized calcium-modified hematite is a spherical particle with a particle size of about 500 nm. The material has a loose and porous structure and a specific surface area of ​​250.64 m 2 / g, and the average pore size is about 30nm.

[0046] Comparative Example: Preparation of Hematite, Calcium-doped Hematite and Porous Hematite

[0047] Synthesis of hematite: Weigh 10.81g of ferric chloride hexahydrate, dissolve it in 200ml of 96% ethanol, add sodium hydroxide solution until pH=12, transfer the resulting suspension into a reactor, and react at 180℃ for 24h. After the reaction is completed, cool the mixed solution to room temperature and centrifuge to obtain the solid material produced by the reaction. Soak it with 0.25mol / L HCl for 10min to remove the poorly crystallized iron oxides; wash it with deionized water and dry it to obtain hematite.

[0048] Synthesis of calcium-doped hematite: Weigh 9.2g of ferric chloride hexahydrate and 0.67g of anhydrous calcium chloride (Ca / (Fe+Ca)=15mol%) and dissolve them in 200ml of 96% ethanol, add sodium hydroxide solution until pH=12, transfer the resulting suspension into a reactor, and react at 180°C for 24h. After the reaction is completed, cool the mixed solution to room temperature and centrifuge to obtain the solid material produced by the reaction. Soak with 0.25mol / L HCl for 10min to remove poorly crystallized iron oxides and calcium adsorbed on the surface; wash with deionized water and dry to obtain calcium-doped hematite.

[0049] Synthesis of porous hematite: Weigh 10.81g of ferric chloride hexahydrate, dissolve it in 200ml of 96% ethanol, add 0.3g of monodisperse silica nanoparticles prepared in Example 1 to the mixed solution, mix it by ultrasonic for 1 hour, add sodium hydroxide solution until pH=12, transfer the obtained suspension into a reactor, and react at 180°C for 24h. After the reaction is completed, cool the mixed solution to room temperature and centrifuge to obtain the solid material produced by the reaction. Soak it with 0.25mol / L HCl for 10min to remove poorly crystallized iron oxides and calcium adsorbed on the surface; then soak it with 2mol / L sodium hydroxide for 12h to remove the silica nanoparticles, wash it with deionized water and dry it to obtain porous hematite.

[0050] Example 3: Comparison of porous calcium-doped hematite, hematite, calcium-doped hematite and porous hematite

[0051] The porous calcium-doped hematite prepared in Example 2 and the hematite, calcium-doped hematite and porous hematite prepared in the comparative example were characterized by XRD, and the results were as follows: Figure 6 The specific surface area of ​​each material was tested, and the results are shown in Table 1. It can be seen that porous calcium-doped hematite has a higher specific surface area than other materials.

[0052] Table 1 Specific surface area of ​​different materials

[0053]

[0054] Example 4: Preparation of hematite or porous hematite with different calcium doping amounts

[0055] Synthesis of hematite with different calcium doping amounts:

[0056] 10.27g of ferric chloride hexahydrate and 0.22g of anhydrous calcium chloride ((Ca / (Fe+Ca)=5mol%), 9.73g of ferric chloride hexahydrate and 0.44g of anhydrous calcium chloride ((Ca / (Fe+Ca)=10mol%) were weighed and dissolved in 200ml of 96% ethanol, and sodium hydroxide solution was added dropwise until pH=12. The resulting suspension was transferred to a reactor and reacted at 180°C for 24h. After the reaction was completed, the mixed solution was cooled to room temperature and centrifuged to obtain the solid substance produced by the reaction. It was soaked in 0.25mol / L HCl for 10min to remove poorly crystallized iron oxides and calcium adsorbed on the surface; it was washed with deionized water and dried to obtain calcium-doped hematite.

[0057] Synthesis of porous hematite with different calcium doping amounts:

[0058] 10.27g of ferric chloride hexahydrate and 0.22g of anhydrous calcium chloride ((Ca / (Fe+Ca)=5mol%), 9.73g of ferric chloride hexahydrate and 0.44g of anhydrous calcium chloride ((Ca / (Fe+Ca)=10mol%) were weighed and dissolved in 200ml of 96% ethanol, 0.3g of the monodisperse silica nanoparticles prepared in Example 1 was added to the mixed solution, ultrasonically mixed for 1 hour, sodium hydroxide solution was added dropwise until pH=12, the resulting suspension was transferred to a reactor, and reacted at 180°C for 24h. After the reaction was completed, the mixed solution was cooled to room temperature and centrifuged to obtain the solid matter produced by the reaction. It was immersed in 0.25mol / L HCl for 10min to remove poorly crystallized iron oxides and calcium adsorbed on the surface; it was immersed in 2mol / L sodium hydroxide for 12h to remove the silica nanoparticles, washed with deionized water and dried to obtain porous hematite with different calcium doping amounts.

[0059] When Ca / (Ca+Fe)>15mol%, only amorphous iron oxides can be produced, which have poor stability and cannot form hematite.

[0060] Example 5: Application of porous calcium-doped hematite in cadmium ion adsorption

[0061] The calcium-modified hematite prepared in Example 2 was weighed and added to a 20 mmol / L MOPS solution with a pH of 7 to obtain a calcium-modified hematite suspension with a concentration of 1 g / L. A 1 g / L cadmium nitrate solution was used as a stock solution and added to the calcium-modified hematite suspension to make the cadmium ion concentration 5 mg / L, and a fixation experiment was performed at room temperature.

[0062] Sampling was performed at specified time points, and the supernatant (Dissolved Cd) was obtained by centrifugation. A certain amount of nitric acid with a pH of 4 was added to the solid phase and immersed for 12 hours (immersion was repeated three times) to remove the cadmium adsorbed on the surface, and the supernatant (Extracted Cd) was obtained by centrifugation. Finally, 6 mol / L hydrochloric acid was added to the solid phase to digest the solid and obtain the cadmium that entered the mineral structure (Nonextraced Cd). All liquids were filtered through a 0.22 μm filter membrane and the cadmium ion concentration was determined using ICP-MS.

[0063] The results are as follows Figure 7 As shown, dissolved cadmium can be quickly fixed on the surface of the material, and gradually replaces calcium in the structure as the reaction proceeds (the concentration of calcium ions in the solution is detected to increase during the reaction), and finally the cadmium is fixed in the hematite structure, greatly reducing its bioavailability. In addition, under acidic conditions of pH = 4, the cadmium ions are still stably fixed.

[0064] As a comparison, the same experiment of fixing cadmium was carried out using the materials in the comparative example according to the above steps. Figure 8-10 As shown in the figure, hematite mainly fixes cadmium in the form of surface adsorption. After being etched into a porous structure, the adsorption of cadmium is greatly increased due to the increase in specific surface area. Calcium-doped hematite can fix cadmium in the structure through an isomorphous substitution mechanism. After being etched into porous calcium-doped hematite, the utilization rate of calcium in the structure is improved, and the amount of cadmium fixed in the structure is significantly increased.

[0065] Hematite can only fix cadmium through surface adsorption. The porous hematite has an increased specific surface area, which increases the contact area with the sample to be treated, thereby increasing the amount of cadmium adsorbed. Calcium-doped hematite can fix cadmium in its structure through isomorphous substitution. Comparing the data in the figure, it can be seen that calcium-doped hematite and porous calcium-doped hematite both show higher cadmium adsorption than undoped hematite; in particular, porous calcium-doped hematite can significantly increase the amount of cadmium fixed in its structure due to the increase in specific surface area.

[0066] Embodiment 6:

[0067] Adsorption isotherm experiment was carried out using the materials prepared in Example 2 and the comparative example

[0068] The material was dispersed in a 20mmol / L MOPS solution with a pH of 7 to obtain a suspension with a concentration of 0.2g / L. Different amounts of cadmium stock solution were added, and the initial concentrations of cadmium were set to 5mg / L, 10mg / L, 20mg / L, 100mg / L, 200mg / L, 300mg / L, and 400mg / L. After the reaction reached equilibrium after 120h, the supernatant was taken and filtered through a 0.22 micron filter membrane, and the cadmium concentration was determined using ICP-MS. The adsorption data obtained were fitted using the Langmuir model, and the results are as follows: Fig.11 As shown, the correlation coefficient shows that the fit is good. According to the Langmuir model fitting results, the maximum adsorption capacity (q m ), and the results are shown in Table 2, which shows that etching hematite into a porous structure can significantly increase the adsorption capacity.

[0069] Table 2 Maximum adsorption capacity of different materials

[0070]

[0071] Embodiment 7:

[0072] The calcium-modified hematite prepared in Example 4 was used according to the method of Example 5 to detect the difference in the effect of calcium-modified hematite with different calcium doping amounts on fixing cadmium ions in the structure. Fig.12 As shown, the amount of cadmium fixed in the structure is positively correlated with the amount of calcium doping, and the porous structure improves the fixed amount of cadmium and the utilization rate of calcium.

[0073] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made according to the scope of application of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing porous calcium-doped hematite, characterized in that: The iron salt, calcium salt and hard template are mixed, the pH value is adjusted to 12, and a crystallization reaction is carried out at 180°C. The obtained product is treated with acid and alkali to remove the hard template in the crystal structure, thereby obtaining porous calcium-doped hematite.

2. The method for preparing porous calcium-doped hematite according to claim 1, characterized in that: The hard template is monodisperse silica nanoparticles.

3. The method for preparing porous calcium-doped hematite according to claim 2, characterized in that: Anhydrous ethanol and tetraethyl orthosilicate were mixed in a volume ratio of 20:1 to prepare solution A; anhydrous ethanol and ammonia water were mixed in a volume ratio of 15.5:1 to prepare solution B; A:B:water was mixed in a volume ratio of 6:6.6:1, and the mixture was stirred at 30°C for 12 hours to obtain monodisperse silica nanoparticles that can be used as a hard template.

4. The method for preparing porous calcium-doped hematite according to any one of claims 1 to 3, characterized in that: The specific steps are as follows: Step 1: Anhydrous ethanol and tetraethyl orthosilicate are mixed in a volume ratio of 20:1 to prepare solution A; Anhydrous ethanol and ammonia water are mixed in a volume ratio of 15.5:1 to prepare solution B; A: B: water are mixed in a volume ratio of 6: 6.6: 1, water is added to solution B to form a mixed solution, and solution A is then added dropwise to the mixed solution, and the reaction is stirred at 30°C for 12 hours to obtain monodisperse silica nanoparticles that can be used as a hard template; Step 2: adding ferric chloride and calcium chloride to ethanol, the total metal ion concentration is 0.2 mol / L, and the molar ratio of iron ion to calcium ion is 85-95:15-5; adding monodisperse silica nanoparticles to the mixed solution, ultrasonically mixing, and adjusting the pH value to 12 with sodium hydroxide; Step 3: The suspension was transferred into a reactor and reacted at 180°C for 24 hours; the obtained solid material was added into 0.25 mol / L HCl and immersed for 30 minutes; Step 4: Add the solid product into a 2 mol / L sodium hydroxide solution, immerse for 12 h to obtain a porous structure, and dry to obtain calcium-modified hematite.

5. A porous calcium-doped hematite, characterized in that: Based on hematite, calcium ions are doped into the crystal structure and etched to form a porous structure.

6. The porous calcium-doped hematite according to claim 5, characterized in that: The calcium-modified hematite is prepared by the preparation method of calcium-modified hematite described in any one of claims 1 to 4.

7. Use of the porous calcium-doped hematite according to claim 5 or 6 in removing farmland soil pollution.

8. The use according to claim 7, characterized in that: Used for removal of cadmium pollution in rice fields.